Performance and innovation in the public sector managing for results - Berman, Evan M.; Hijal-Moghrabi, Imane (Routledge, 2023)
"Managing for results is ever more has become an increasingly important for the success of public organizations. Performance and Innovation in the Public Sector is a comprehensive textbook that examines a broad range of performance strategies. Today's public managers require a broad toolkit and deep, current understanding of the following: performance management, digital government, collaboration, strategic planning, innovation, lean government, and managing people for performance. This book provides a thorough overview of broad paradigms and their emergence, each strategy along with examples and up-to-date applications, and appreciation for the diverse contexts of public organizations resulting in varied and tailored improvements. Each chapter assists students in applying each tool at work. Performance and Innovation in the Public Sector provides a balance of scholarship and practice, offers flexibility for instructors and is written in a style that students and professionals much appreciate. This revised, much anticipated third edition includes increased emphasis on improving governance and innovation, and up-to-date examples that increase appreciation for performance in diverse public sector settings"--
Includes bibliographical references and index. - Description based on online resource; title from digital title page (viewed on January 31, 2023)
Keywords: Government productivity; Administrative agencies -- Management; Nonprofit organizations -- Management; Administration publique; Productivité; Administration publique; Gestion; Associations sans but lucratif; Gestion; POLITICAL SCIENCE / General; TRANSPORTATION / Railroads / General; Administrative agencies; Management; Nonprofit organizations; Management